Digital ethnography as a way to explore information grounds on Twitter - Talip, Bazilah A.; Narayan, Bhuva; Edwards, Sylvia L.; Watson, Jason (Qualitative and Quantitative Methods in Libraries; Vol 5 No 1 (2016): March 2016 Issue, 2017)
Information grounds are social settings where information, people, and place come together to create information flow within a physical environment (Karen E. Pettigrew, 1998). Information grounds also facilitate the opportunistic discovery of information within social settings created temporarily by people gathered for some purpose other than seeking information, but the social environment stimulates spontaneous information sharing (K. E. Pettigrew, 1999), such as in hair salons, doctor‘s waiting rooms and other public places. Professional and scholarly use of social media is a rapidly emerging area of research. In this regard, qualitative analysis of data gathered from Twitter is a relatively unexplored area of Library and Information Science (LIS) research. This paper details the results of a qualitative study of Twitter using digital ethnography, in order to investigate the use of Twitter by IT professionals in forming communities of practice. This study is relevant to Library and Information Science (LIS) research as LIS professionals are part of the IT community of practice. This study used information grounds theory (K. E. Fisher, 2005) to explore Twitter as an online information ground.  The research used online observation – conceptualised here as online ethnography or digital ethnography – and interviews to collect data. The online observations helped the researcher to understand the norms and culture of the participants along with patterns of behaviour. Interviews were used to understand the information grounds of the virtual environment through the participants‘ individual perspectives and their information experiences. A total of eleven participants were interviewed after a total of 734 tweets from these same participants were downloaded and analysed. Both interview and Twitter data were analysed using constructivist grounded theory (Charmaz, 2006). The findings highlight a variety of information sharing types, the role of information sharing in professional contexts, and the influences of Twitter on communication and social engagement, including a counterintuitive finding that professionals use Twitter not so much to seek or share information as much as to seek out a network of like-minded people. The significance of this study is in providing a fundamental understanding of theways in which social media is used for professional reasons. It also proposes a systematic, qualitative data collection and data analysis approach to future research around Twitter and social media in general. This contribution not only helps LIS researchers, but can also help information professionals in the use of social media for professional purposes.